Pengaruh model pembelajaran kooperatif tipe stad melalui teknik quick on the draw terhadap kemampuan komunikasi matematis siswa kelas vii smpn 3 Talamau kabupaten pasaman barat - Melia Roza, M.Pd (E-Tech : Jurnal Ilmiah Teknologi Pendidikan, 2018)
This study originated from the problem of low communication skills of students in SMPN 3 Talamau. This is caused partly because the learning is still centered on the teacher. Students are not actively involved in the multiplication concepts or ideas of mathematics. To overcome these problems used cooperative learning model STAD through techniques Quick On The Draw. This study aims to determine the effect of cooperative learning STAD type through techniques Quick On The Draw the students' mathematical communication skills. This type of research is a Quasi Exsperiment. The study population was all students of class VII SMPN 3 Talamau enrolled in the second semester of the school year 2012/2013. Sample selection is done by random sampling so chosen as an experimental class is the class VII1 and as the control class is the class VII2. The research instrument was the test the ability of the initial and final test in the form of a matter of mathematical communication skills. Data analysis was performed using the t test and ANOVA two-way interaction. The analysis showed that: the ability of mathematical communication students taught by cooperative learning model STAD through techniques Quick On The Draw better than students taught by conventional learning, communication skills mathematically capable students beginning high and low taught by cooperative learning model STAD through techniques Quick on the Draw better than students taught by conventional learning and there is no interaction between the learning model and the initial capabilities of the students' mathematical communication skills.